2020
DOI: 10.1108/ijphm-12-2018-0064
|View full text |Cite
|
Sign up to set email alerts
|

Prescribers’ and dispensers' views about generic medicines and international non-proprietary name prescribing – a mixed methods study in Portugal

Abstract: Purpose This study aims to explore the views of pharmacy professionals (PPs) in Portugal about generic medicines and international non-proprietary name (INN) prescribing and compare them with the views of general practitioners (GPs). Design/methodology/approach A self-administered questionnaire was used to collect data from a sample of 185 community PPs and 85 GPs. Their perceptions were examined using a five-point Likert scale applied to statements focusing on five main topics of interest: motivation, safet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The system should be simplified to make it clearer to the customer and easier for pharmacists to execute. In a Portuguese study, for example, pharmacy professionals considered it difficult to explain the frequent change in prices to customers [ 48 ]. Similar findings were also made in this study, as continued price fluctuations and changes in the reference price band were reported to complicate counselling.…”
Section: Discussionmentioning
confidence: 99%
“…The system should be simplified to make it clearer to the customer and easier for pharmacists to execute. In a Portuguese study, for example, pharmacy professionals considered it difficult to explain the frequent change in prices to customers [ 48 ]. Similar findings were also made in this study, as continued price fluctuations and changes in the reference price band were reported to complicate counselling.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent mixed-methods study showed negative perceptions of general practitioners toward generic drugs in terms of quality, efficacy, and safety. 10 In low- and middle-income countries, pharmacists have limited capacity to switch to lower-cost options without referring to doctors and patients’ acceptance of substitution is essential since most payments are out-of-pocket. 11,12 Generic drugs and biosimilars have many similarities; however, they differ in several aspects such as characteristics, production, and interchangeability.…”
Section: Introductionmentioning
confidence: 99%